Canadian National Union Presidents: An Empirical Study - Solomon, Norman; Andiappan, Palaniappan; Shand, Dan (Relations industrielles / Industrial Relations, 1986)
This study examines personal and organizational factors affecting the rise to office of presidents of Canadian national unions.